The Effect of Organizational Structure and Ngo-Ngo Relationships on Sustainability in NGOs - Metin, Hasan (European Journal of Economics and Business Studies, 2017)
This study analyses the statistical relation among Sustainability, Organizational Structure and NGO-NGO relationships within the concept of Non-Governmental Organization (NGOs). Sustainability is the dependent variable of the study whereas independent variables are Organizational Structure and NGO-NGO relationships. Sustainability is conceptualized as the survival of the NGOs within the study. Within organizational structure the emphasis is on having either mechanistic or organic structure and finally NGO-NGO relationships refer to the level of closeness to the other NGOs as participation events of the other NGOs, organizing the events together and becoming members of NGO unions like federations and Confederations. Results indicate that both independent variables (Organizational Structure and NGO-NGO relationships) have positive affect on the sustainability of the NGOs. Linear regression has been utilized in order to determine the effect of the independent variables of the study and the dependent variable. Statistical Package for the Social Sciences (SPSS) has been used for the analysis.